Numerical Simulation Study of Droplet Atomization Behavior in Tubular Atomizer Elements - Kang, Zhenqiang; Zhang, Liang; Chen, Xin (Scientific Journal of Technology, 2026)
Atomizing a liquid solvent into micron-sized droplets can significantly increase the specific contact area between the gas phase and the liquid phase. This paper employs CFD methods to investigate the atomization performance of a tubular natural gas atomizer and analyzes the effects of four different gas flow velocities (18 m/s–23 m/s) on the atomization efficiency. The results indicate that the use of a Venturi channel structure, where peak gas velocities in the throat region exceed 90–110 m/s, effectively breaks the liquid into small droplets. In the high-frequency pulsation transition zone at 18 m/s and 23 m/s, irregular turbulent diffusion enhances interphase mixing, rapidly entraining fragmented microdroplets of triethylene glycol into every corner of the gas phase, thereby significantly reducing concentration polarization within the flow field. The wake effect generated by the hollow channel results in a higher DPM concentration in the region around the central axis. A comparative analysis of the four velocities revealed that 18 m/s is more suitable for droplet atomization.